Disturbed Ecologies: Photography, Geopolitics, and the Northern Landscape in the Era of Environmental Crisis - Goldie, Chris; White, Darcy; Peck, Julia (transcript, 2023)
The imaginaries of northern landscape have not remained static in the era of ecological crisis but play a pivotal function within the geopolitics of visual representation. Such imaginaries can sanction those dominant discourses that frame environmental catastrophe as the consequence of undifferentiated human activity, but, it is argued, they also have the capacity to represent a complexity and heterogeneity frequently absent from this broad discursive field. The contributors to this volume engage with the practice, curation and utilization of photography and other lens-based media, to examine the critical role of visual culture in shaping and interrogating conceptions of environmental catastrophe.